Development and Validation of Bioanalytical HPLC Method For Estimation of Telmisartan In Rat Plasma: Application To Pharmacokinetic Studies - Patel, Jaydeep M; Dhingani, Anjali P; Garala, Kevin C; Raval, Mihir K; Sheth, Navin R (Dhaka University Journal of Pharmaceutical Sciences, 2013)
A simple, specific, sensitive and rapid reversed phase high performance liquid chromatographic (HPLC) method has been developed and validated for the determination of telmisartan in small volumes of rat plasma. Biological sample preparation involving simple extraction with organic solvent, followed by dilution with mobile phase was adopted to eliminate any chromatographic solvent effects. The method was proven to be linear over a plasma concentration range of 10 to 1000 ng/mL with a mean correlation coefficient of 0.9942. The limit of detection and the limit of quantification of the newly developed method were determined to be 1 ng/mL and 10 ng/mL, respectively. The method was successfully applied to assess pharmacokinetic parameters of telmisartan in Wister rats following a single oral dose (1.8 mg/kg, b.w.). The developed method was established as a rapid analytical tool in a pharmacokinetic study as it required short retention time, high precision, sensitivity and small volumes of plasma for analysis. DOI: http://dx.doi.org/10.3329/dujps.v11i2.14562 Dhaka Univ. J. Pharm. Sci. 11(2): 121-127, 2012 (December)